Competence of State Administrative Court in Adjudicating Presidential Decree as Head of State - Muhammad Fauzan; Ali Imran Nasution (Journal of Law, Politic and Humanities, 2025)
The position of the President in the presidential system places the President's function as head of state and head of government. The unification of those functions doesn’t negate the differences in the President’s functions as head of state and head of government. This affects the President's authority in issuing decrees. The absence of such affirmation creates legal uncertainty over the resolution of the President's decision, especially the President's decision as head of state. The formulation of the problem raised is 1) how is the model of the using Presidential Decrees in terms of the President’s function as head of state and head of government; and 2) how is the competence of State Administrative Court in adjudicating Presidential Decree as head of state. The research method used normative juridical with a statutory and contextual approach. The results show there are different models of using Presidential Decrees in his position as chief of state and chief of government. Then, the President's decision regarding his position as chief of state becomes a necessity to be differentiated with following elements, First, the President issued it in his capacity as head of state, Second, the President did not have beslissing in issuing it, Third, the decision was issued by the President based on his authority obtained by attribution from the Constitution